Vast as the sea: Hebrew poetry and the human condition - Hildebrandt, Samuel (1517 Media, 2023)
The poetry of the Old Testament articulates the painful experiences of being human. Vast as the Sea shows how texts like Job, Jeremiah, and the Psalms provide honest and healing expressions for life's struggles. This book is a rich resource for scholars and readers of the Bible, as well as for psychologists and pastoral counselors